PENGARUH TOTAL QUALITY MANAGEMENT DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN PADA PTPN V SEI PAGAR KABUPATEN KAMPAR - Akbar Ridho; Samsir Samsir; M.Marpaung Jonnes Rio (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of the influence of Total Quality Management and Transformational Leadership on Employee Performance at PTVN V SeiPagar, Kampar Regency. The population in this study is the employees of PTVN V SeiPagar Kampar Regency, data collection was carried out using a questionnaire with a sample of 103 people, using purposive sampling technique. The analysis in this study uses Multiple Linear Regression with the help of SPSS 21 program. The results showed that: 1) Total Quality Management (TQM) had a significant effect on employee performance at PT. Perkebunan Nusantara V (PTPN V) KebunSeiPagar, Kampar Regency, Riau. 2) Transformational Leadership has a significant effect on Employee Performance at PT. Perkebunan Nusantara V (PTPN V) KebunSeiPagar, Kampar Regency, Riau. For further research, work environment variables and work motivation can be added to employee performance.Keywords: Total Quality Management, Transformational Leadership, Employee Performance